TikTok as an Effective Tool for English Language Learning: A Digital Ethics Perspective - Ninik Suryatiningsih; Dwi Priyo Widodo; Baiduri Baiduri; Ribut Wahyu Eriyanti (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The integration of TikTok as a tool in English language learning has rapidly expanded due to its engaging, short-form video format and the platform’s ability to foster creativity, student participation, and peer interaction. Despite this growth, limited scholarly attention has been paid to the digital ethical challenges posed by TikTok’s use in educational settings, particularly those related to data privacy, algorithmic bias, content moderation, and disinformation. Methodology: This research employs a systematic literature review approach, synthesizing findings from relevant studies on TikTok in education, with emphasis on English language instruction. The selection process follows PRISMA guidelines to ensure comprehensive and unbiased coverage of relevant literature. Main Findings: Findings indicate that TikTok significantly enhances learners’ speaking, listening, and digital communication skills while encouraging collaborative and socially interactive learning environments. However, ethical issues—such as exposure to inappropriate content, misinformation, lack of algorithm transparency, and student data vulnerabilities—emerge as critical concerns that require careful pedagogical management. Novelty/Originality of this study: This study presents a novel conceptual framework for integrating TikTok into English language education ethically and responsibly, positioning it at the intersection of digital pedagogy and media ethics. It advocates for the inclusion of digital literacy and ethics training within the curriculum to equip educators and students to engage with social media tools in a more informed and secure manner.